Teaching in a Shared Classroom: Unveiling the Effective Teaching Behavior of Beginning Team Teaching Teams Using a Qualitative Approach - Dries Mariën; Ruben Vanderlinde; Elke Struyf (MDPI AG, 2023)
This study aims to gain insight into the experiences of beginning team teaching teams and the dimensions of effective teaching behavior that are perceived as clear added value in their pedagogical practices. Sixteen beginning team teaching teams from twelve different elementary schools participated in team interviews. The more complex dimensions of effective teaching behavior, based on the International Comparative Analysis of Learning and Teaching (ICALT) framework, such as adaptive teaching and activating learning, were perceived as clear added value in their team teaching practices. Meanwhile, the more basic teaching dimensions-including efficient classroom management, providing clear instruction, and creating a safe and stimulating learning climate-were reported to a lesser extent.